Political protest in the Congo : the Parti solidaire africain during the independence struggle - Weiss, Herbert F. (Princeton University Press, 1967)
In this first detailed study of the PSA, a party that has played a crucial role in Congolese politics, Weiss describes the growth of political parties from 1957 to 1960, and gives a history of the PSA, and of the anti-colonial protest in the Kwango-Kwilu area. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.